Kejahatan, Moralitas dan Dekolonisasi: Analisis Perbandingan Kritis terhadap Reformasi Hukum Pidana di Indonesia dan India - Aditi Singh Kavia; Karan Singh Chouhan (Jurnal Penelitian Hukum De Jure, 2025)
The criminal laws have undergone a comprehensive reform with the enactment of the Kitab Undang-Undang Hukum Pidana (KUHP), 2023 in Indonesia and  Bharatiya Nyaya Sanhita (BNS), Bharatiya Nagarik Suraksha Sanhita (BNSS), and Bharatiya Sakshya Adhiniyam (BSA), 2023 in India. Those circumstances have raised serious questions concerning human rights. The newly enacted Criminal laws were introduced as a comprehensive reform to supersede the outdated colonial-era legislation, with the intention of dismantling colonial legacy. This study endeavors to conduct a critical evaluation of the extent to which recent criminal law reforms in Indonesia and India conform to the principles of decolonization. Specifically, it examines whether these reforms aligns with legal morality and human rights, evaluating whether they dismantle colonial legal legacies or inadvertently reinforce them. Furthermore, it aims to conceptualize various frameworks of morality, its nexus with law and explores the morality dilemmas by situating the study within the theoretical framework of decolonization. The research follows a comparative and doctrinal legal research approach, critically analyzing offenses against state, morality and religion-based offenses such as blasphemy, adultery, sedition, homosexuality, abortion among others. The findings of the study reveal that reforms of criminal codes have instead reinforced colonial morality and has disproportionality affected human rights of minorities. Through this study, the author concludes that true decolonization can be achieved when the colonial structures are questioned, colonial institutions are dismantled and the laws are in alignment with the international human rights standards. It is also recommended that the reform process should be continuous, democratic, empirical and ensure traditional belief and  moralities are respected without infringing on individual rights.